Psychological functioning of patients at earlier grades of COPD - Marques, Alda (2020)
Chronic Obstructive Pulmonary Disease (COPD) has a major impact on patients' psychological function. Anxiety and depression have been reported in approximately 50% of patients with COPD. However, most of the available data is related to patients at advanced grades. The aim of this study was to assess the presence of anxiety and depression in patients at earlier grades of COPD. A cross-sectional study was carried out with 98 outpatients with COPD (GOLD 1 and GOLD 2) in the central region of Portugal. Socio-demographic and functioning data were collected with a questionnaire based on the International Classification of Functioning, Disability and Health. Spirometry was also performed. Anxiety and depression were evaluated using the Hospital Anxiety and Depression Scale (HADS). Descriptive statistics and χ2 tests were applied using PASW Statistics version 18.0. Participants mean age was 64.46±12.68 years old and mean FEV1 % predicted was 75.59±15.88. Approximately half of the sample (n=53; 54.08%) had symptoms of anxiety (HADS-A≥8), 40.82%(n=40) of depression (HADS-D≥8) and 31.63%(n=31) of both. The grade of COPD and gender were not found to be significantly associated with anxiety or depression. However, anxiety was significantly associated with severe dyspnea (p=0.025) and depression with higher difficulties in walking (p=0.001) and higher restrictions in participating in community life (p=0.049). Patients with COPD at earlier grades have high levels of anxiety and depression. Knowledge about the psychological functioning of patients with COPD will inform psycho-education and respiratory physiotherapy interventions, to support patients and improve their adjustment to the disease.